Detection of Candidatus Liberibacter asiaticus and five viruses in individual Asian citrus psyllid in China - Liu, Luqin; Chen, Jing; Jiang, Junyao; Liang, Jiamei; Song, Yaqin; Chen, Qi; Yan, Fuling; Bai, Ziqin; Song, Zhen; Liu, Jinxiang (Frontiers in Plant Science, 2024)
Asian citrus psyllid (ACP, Diaphorina citri) is an important transmission vector of “Candidatus Liberibacter asiaticus” (CLas), the causal agent of Huanglongbing (HLB), the most destructive citrus disease in the world. As there are currently no HLB-resistant rootstocks or varieties, the control of ACP is an important way to prevent HLB. Some viruses of insect vectors can be used as genetically engineered materials to control insect vectors. To gain knowledge on viruses in ACP in China, the prevalence of five RNA and DNA viruses was successfully determined by optimizing reverse transcription polymerase chain reaction (RT-PCR) in individual adult ACPs. The five ACP-associated viruses were identified as follows: diaphorina citri bunyavirus 2, which was newly identified by high-throughput sequencing in our lab, diaphorina citri reovirus (DcRV), diaphorina citri picorna-like virus (DcPLV), diaphorina citri bunyavirus (DcBV), and diaphorina citri densovirus-like virus (DcDV). DcPLV was the most prevalent and widespread ACP-associated virus, followed by DcBV, and it was detected in more than 50% of all samples tested. DcPLV was also demonstrated to propagate vertically and found more in salivary glands among different tissues. Approximately 60% of all adult insect samples were co-infected with more than one insect pathogen, including the five ACP-associated viruses and CLas. This is the first time these viruses, including the newly identified ACP-associated virus, have been detected in individual adult ACPs from natural populations in China’s five major citrus-producing provinces. These results provide valuable information about the prevalence of ACP-associated viruses in China, some of which have the potential to be used as biocontrol agents. In addition, analysis of the change in prevalence of pathogens in a single insect vector is the basis for understanding the interactions between CLas, ACP, and insect viruses.